1991
DOI: 10.1002/art.1780340105
|View full text |Cite
|
Sign up to set email alerts
|

Chondrons from articular cartilage. III. Morphologic changes in the cellular microenvironment of chondrons isolated from osteoarthritic cartilage

Abstract: Chondrons were isolated from human and canine osteoarthritic cartilage using low-speed homogenization techniques. Changes in chondron morphology were evaluated using differential interference-contrast microscopy, phase-contrast microscopy, and histochemical and ultrastructural methods. Chondrocyte viability was assessed using fluorescein diacetate staining, and chondron metabolism was investigated using autoradiography. The results suggest that initial changes in the collagen and proteoglycan distribution with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
69
0
4

Year Published

1995
1995
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 43 publications
0
69
0
4
Order By: Relevance
“…Disruption of the pericellular matrix exposes chondrocytes to collagen type II, resulting in abnormal chondrocyte activities such as activation of DDR2. Poole et al 21 have reported morphologic changes of the pericellular matrix of chondrocytes in the OA car- . Collagen type VI was present in both TRE-DDR2 and ComptTA;TRE-DDR2 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of the pericellular matrix exposes chondrocytes to collagen type II, resulting in abnormal chondrocyte activities such as activation of DDR2. Poole et al 21 have reported morphologic changes of the pericellular matrix of chondrocytes in the OA car- . Collagen type VI was present in both TRE-DDR2 and ComptTA;TRE-DDR2 mice.…”
Section: Discussionmentioning
confidence: 99%
“…In recent papers, Poole et al [15][16][17][18] suggested that chondrocytes from hyaline cartilage and their specialized microenvironment form a unit termed "chondron" . The chondron is argued to be a primary functional and metabolic unit of hyaline cartilages which regulates the development, maintenance and repair of hyaline cartilage [15][16][17][18]. In the cartilage tissues examined in the present study, it is possible that the pericellular matrices could correspond to specialized microenvironments of the chondron.…”
Section: Discussionmentioning
confidence: 99%
“…The chondron has been shown to contain type II, III, VI and IX collagens, the proteoglycan aggregate components (such as chondroitin sulfates A and C, keratan sulfate, coreprotein and hyaluronan binding region) and glycoprotein (such as fibronectin) [16][17][18] . Furthermore, it has been known that the collagen fibers in the cartilage matrices bind to proteoglycan aggregates [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations